Board of directors, firm performance and the moderating role of family control in JORDAN - Makhlouf M.H.; Laili N.H.; Ramli N.A.; Al-Sufy F.; Basah M.Y. (Allied Business Academies, 2024)
Indexed by SCOPUS/ERA